Correction: Poly(acrylic acid)-mediated synthesis of cerium oxide nanoparticles with variable oxidation states and their effect on regulating the intracellular ROS level - Ju, Xiaohui; Kalbacova, Marie Hubalek; Šmíd, Břetislav; Johánek, Viktor; Janata, Martin; Dinhová, Thu Ngan; Bělinová, Tereza; Mazur, Michal; Vorokhta, Maryna; Strnad, Ladislav (Journal of materials chemistry. B, 2021)
Correction for 'Poly(acrylic acid)-mediated synthesis of cerium oxide nanoparticles with variable oxidation states and their effect on regulating the intracellular ROS level' by Xiaohui Ju et al., J. Mater. Chem. B, 2021, 9, 7386-7400, DOI: 10.1039/D1TB00706H.